2020
DOI: 10.1002/ece3.7009
|View full text |Cite
|
Sign up to set email alerts
|

Next‐generation field courses: Integrating Open Science and online learning

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 88 publications
(126 reference statements)
0
21
0
Order By: Relevance
“…In keeping with the cognitive apprenticeship and development theme of the course, the course also aims to provide opportunities for researchers, especially those early in their careers, to experience and grow from field-based teaching (Geange et al, 2021). This has required a conscious professional development focus, and application of the apprenticeship model, to bring early career researchers into the teaching team, and to embrace high turnover in the broader staff group.…”
Section: How the Course Structure Achieves The Course Aimsmentioning
confidence: 99%
See 2 more Smart Citations
“…In keeping with the cognitive apprenticeship and development theme of the course, the course also aims to provide opportunities for researchers, especially those early in their careers, to experience and grow from field-based teaching (Geange et al, 2021). This has required a conscious professional development focus, and application of the apprenticeship model, to bring early career researchers into the teaching team, and to embrace high turnover in the broader staff group.…”
Section: How the Course Structure Achieves The Course Aimsmentioning
confidence: 99%
“…Field courses are an immersive example of research-led enquiry-based learning that can provide students with their first exposure to independent research (Geange et al, 2021). Field courses also provide particular opportunities for undergraduates to experience, recognise and experience integrative learning i.e., learning that connects disparate concepts or disciplines, as opposed to fragmented or compartmentalised learning (Durrant and Hartmann, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID‐19 situation has shown that as researchers we can do a lot of our work and collaborate with other researchers remotely. But working remotely sometimes raises a lot of challenges in terms of “real‐time” collaboration (Geange et al., 2020; Holt et al., 2020; Trogisch et al., 2020). Online collaboration tools enable us to work together efficiently, either through facilitating communication, the sharing or storage of files and documentation, and the capacity to work in a coordinated manner (Burgio et al., 2020).…”
Section: Remote Collaborations: Online Platforms Version Control and Reproducibility Toolsmentioning
confidence: 99%
“…Conversely, empirical activities, such as active learning projects (Gahl et al, 2020 ), can be disregarded as less efficient in motivating students into acquiring new knowledge without having to pass an exam. Fortunately, in the current critical context, developing innovative online teaching and learning approaches, and using any available technologies, has become a key priority (Gahl et al, 2020 ; Geange et al, 2020 ; Houtz et al, 2020 ; Richter et al, 2020 ; Van Haeften et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%